The Sanak-Kadang Jodhipati: A New Form of Virtual Radio Listeners Community - Zainal Abidin Achmad; Heidy Arviani; Nobertus Ribut Santoso (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2021)
The purpose of this study was to analyze the shifting form of a community of cultural radio listeners, Sanak Kadang Jodhipati, from an off-line to a virtual community. Since adopting Facebook, YouTube, and audio streaming, Radio Jodhipati FM’s listeners have become part of a networked community. This study used a virtual ethnographic method, which allows researchers to conduct interviews and virtual searches from November 2019 to May 2020. The result shows that Sanak Kadang Jodhipati, as a social community, holds meetings in the Nganjuk Regency and other cities where Radio Jodhipati FM covers wayang kulit shows. As a virtual community, this community is more intensive in communicating through the WhatsApp group during the COVID-19 pandemic. The contents of the communication are not limited to discussing wayang kulit, gendhing, and other Javanese culture, it also addresses health, employment, legal, and political issues. Despite the diverse socioeconomic status, the members do not differentiate the form of communication, as fellow Javanese culture lovers.